Discourse of Gaming: A Conceptual Framework of Gaming as an Interpretive Community. Issue 3 (27th May 2022) - Perreault, Gregory P.; Lynch, Teresa
ABSTRACT: Situating gaming as a cultural practice aimed at constructing issues of power through cultural discussions necessitates a framework of discourse of gaming to explain how meanings around gaming practice develop. Built on the premise that gaming offers multimodal opportunities for interaction, we introduce the discourse of gaming framework to connect processes of boundary work, definition making, and legitimization to the activities of gaming, the gamer's identity, and the consequences of gaming. Through a survey of Reddit gaming fan communities, discourse of gaming here reflects the power perceived outsiders (e.g., journalists, academics, and politicians) have on shaping the discourse.